1982
DOI: 10.1073/pnas.79.6.1854
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen transport parameter in membranes as deduced by saturation recovery measurements of spin-lattice relaxation times of spin labels.

Abstract: Spin-lattice relaxation time (T1) measurements of nitroxide radical spin labels in membranes have been made by using the saturation-recovery technique. Stearic acid and sterol-type labels were used as probes of dimyristoylphosphatidylcholine liposomes from 0 degrees C to 36 degrees C. In the absence of oxygen, the range of variation of T1 over all samples and conditions is about a factor of 3. Heisenberg exchange between oxygen and spin labels is an effective T1 mechanism for the spin labels. The full range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
182
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(184 citation statements)
references
References 15 publications
2
182
0
Order By: Relevance
“…Using the theory of Diamond and Katz (7), we have assessed oxygen permeability across the membrane on the basis of W(x) profiles, assuming that oxygen diffusion is isotropic. We have previously shown that oxygen diffusion is almost isotropic in the liquid-crystalline phase of non-cholesterol-containing membranes (3). Diffusion of oxygen below the pretransition temperature was found to be more rapid in the transverse than in the lateral direction.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…Using the theory of Diamond and Katz (7), we have assessed oxygen permeability across the membrane on the basis of W(x) profiles, assuming that oxygen diffusion is isotropic. We have previously shown that oxygen diffusion is almost isotropic in the liquid-crystalline phase of non-cholesterol-containing membranes (3). Diffusion of oxygen below the pretransition temperature was found to be more rapid in the transverse than in the lateral direction.…”
mentioning
confidence: 91%
“…The buffer was 0.1 M borate at pH 9.5. To ensure that all probe carboxyl groups were ionized in PtdCho membranes, a rather high pH was chosen (3,5,12,13). The structure of PtdCho membranes is not altered at this pH (3,13).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multilamellar vesicles were prepared following the method of Kusumi et al [26]. Phospholipids were dissolved in a 2:1 chloroform methanol mixture then dried with a stream of nitrogen gas and kept under vacuum for at least 14 h. The dried lipids were suspended, when not otherwise specified, in a HEPES 0.1 M, pH 7.2, buffer.…”
Section: Liposome Preparationmentioning
confidence: 99%